2020
DOI: 10.9734/ejnfs/2020/v12i530223
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Practices of Men and Women across Rural-Urban Interface of South Indian Megacity Bangalore

Abstract: Background: Food consumption practices involving dietary diversity, healthy and unhealthy practices have greater influence on nutritional and health status of the individual. Men and women always behave differently and have different consumption pattern due to various factors. Urbanization gradients along rural-urban interface of Bangalore mega city helps for comparative study of these factors. Aims: To compare food consumption practices between men and women across rural-urban interface of Bangalore, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…we should not wash hands before food intake, 26 per cent respondents think that junk and road side food are not healthy and hygienic and nuts and oilseeds should not be avoided in daily diet, egg should not be included in daily diet and we should not avoid drinking direct tap water (22%). Geeta et al [9] reported that in rural area maximum difference for healthy habit score was existed between men (50.8%) and women (44.0%). Average unhealthy habits score was more among women in rural (33.2%) and transition (35.4%) areas, whereas in urban, men had higher score (41.8%).…”
Section: Fig 2 Distribution Of the Respondents By Their Nutritional H...mentioning
confidence: 97%
“…we should not wash hands before food intake, 26 per cent respondents think that junk and road side food are not healthy and hygienic and nuts and oilseeds should not be avoided in daily diet, egg should not be included in daily diet and we should not avoid drinking direct tap water (22%). Geeta et al [9] reported that in rural area maximum difference for healthy habit score was existed between men (50.8%) and women (44.0%). Average unhealthy habits score was more among women in rural (33.2%) and transition (35.4%) areas, whereas in urban, men had higher score (41.8%).…”
Section: Fig 2 Distribution Of the Respondents By Their Nutritional H...mentioning
confidence: 97%
“…Dietary diversity is a summed number of different food groups consumed at a given time, and it is referred as a proxy to food security [44]. The diversity of diets for children mainly depends on crops and livestock diversification and nutrition knowledge that caregivers possess.…”
Section: Chicken Ownership and Dietary Diversity For Childrenmentioning
confidence: 99%